2002
DOI: 10.1021/bi015888y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electron Transfer in the Complex between Fluorescein and a Cognate Engineered Lipocalin Protein, a So-Called Anticalin

Abstract: Anticalins are a novel class of engineered ligand-binding proteins with tailored specificities derived from the lipocalin scaffold. The anticalin FluA complexes fluorescein as ligand with high affinity, and it effects almost complete quenching of its steady-state fluorescence. To study the underlying mechanism, we have applied femtosecond absorption spectroscopy, which revealed excited-state electron transfer within the FluA‚Fl complex to be responsible for the strong fluorescence quenching. On the basis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…For underlabelled FITC-BSA in solution the major decay component is similar to that of uncoupled FITC in solution, but appears to decrease slightly with increasing the number of tags per protein. This could relate to the increased possibility of the tag binding to a site favourable for quenching FITC emission, as has been noted before for various amino acids (mainly tryptophan) with FITC in solution [54] or FITC-labelled protein [58]. For overlabelled FITC-BSA in solution three time components are needed for a good fit and the main component decays with a subnanosecond (0.5 ns) lifetime.…”
Section: Fitc Labellingmentioning
confidence: 86%
“…For underlabelled FITC-BSA in solution the major decay component is similar to that of uncoupled FITC in solution, but appears to decrease slightly with increasing the number of tags per protein. This could relate to the increased possibility of the tag binding to a site favourable for quenching FITC emission, as has been noted before for various amino acids (mainly tryptophan) with FITC in solution [54] or FITC-labelled protein [58]. For overlabelled FITC-BSA in solution three time components are needed for a good fit and the main component decays with a subnanosecond (0.5 ns) lifetime.…”
Section: Fitc Labellingmentioning
confidence: 86%
“…The Coulombic interaction experienced by the reactants and products as they are brought together in the encounter pair are included in equation 10 as being Götz et al 45 applied femtosecond absorption spectroscopy to show that fluorescein is electron photoreduced by either tryptophan or tyrosine after binding to Anticalin, a Lipocalin protein, where the fluorescein trianion radical is formed very quickly in about 400 fs. The G 0 value used by Götz et al is in the same range as found in our work.…”
Section: Dynamic Quenchingmentioning
confidence: 99%
“…Interestingly, the characteristic stationary fluorescence of fluorescein becomes al-most completely quenched on complex formation with FluA (26). This phenomenon has been attributed to an extremely fast and efficient electron transfer between the excited fluorescein dianion and a tryptophan side chain that is tightly packed against its xanthenolone moiety in the ligand pocket, followed by a radiationless backtransfer (29).…”
mentioning
confidence: 99%
“…In the native state emission of the complexed fluorescein is completely quenched, whereas in the denatured state fluorescein regains its high quantum yield (29). Consequently, measurement of the relative fluorescence intensity as a function of pressure at a defined temperature yields the equilibrium constant for denaturation as a function of pressure or vice versa and, hence, the boundary of the phase diagram.…”
mentioning
confidence: 99%